INTERNALIZATION OF THE VALUES OF UNITY AND DIVERSITY THROUGH THE PRESERVATION OF PRAMBANAN TEMPLE AS A CULTURAL HERITAGE - Supriadi; Sufian Assidiq; Rifa Sihabul Muharom; Muhammad Zaenal Arifin; Ade Mahmudin; Moh. Rizalul Akmal (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Prambanan Temple, as one of the world's cultural heritage sites, holds not only historical and architectural significance but also cultural messages that remain relevant in contemporary Indonesian society. This study aims to examine how the preservation of Prambanan Temple can serve as a medium for internalizing the values ​​of unity and diversity within a multicultural context. Amid the challenges of globalization, rising intolerance, and shifting social values, cultural heritage has great potential as an educational tool to strengthen national character. Using a descriptive qualitative approach and literature review, this research explores the symbolic meanings and social roles of Prambanan Temple in fostering awareness of peaceful coexistence and respect for differences. The findings reveal that participatory and education-integrated preservation efforts can enhance a sense of ownership of national cultural identity and encourage younger generations to embrace the values ​​of unity and diversity. Therefore, preserving cultural heritage should not only focus on physical conservation but also be recognized as an essential part of national character development.